Uncle Tom's cabin - McKinley, Caroline; Inden, Hugo.; Tarwater, Penelope; Tarwater, Rebecca; Stowe, Harriet Beecher, 1811-1896.; King-Smith Playhouse and School of Theatre Arts (Washington, D.C.); Richard L. Coe Theater Programs Collection (Library of Congress) (London : Patridge and Oakey, 1953)
The King-Smith Playhouse presents "Uncle Tom's Cabin," a new version in three episodes by Rebecca Tarwater, directed by Caroline McKinley, settings and costumes by Hugo Inden, music by Penelope Tarwater.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Uncle Tom (Fictitious character) -- Drama; Theater programs -- Washington (D.C.); Theater programs -- 1945.